A Novel Thiazolyl Schiff Base: Antibacterial and Antifungal Effects and In Vitro Oxidative Stress Modulation on Human Endothelial Cells. (10th October 2019) - Login, Cristian Cezar; Bâldea, Ioana; Tiperciuc, Brînduşa; Benedec, Daniela; Vodnar, Dan Cristian; Decea, Nicoleta; Suciu, Şoimiţa
Abstract : Schiff bases (SBs) are chemical compounds displaying a significant pharmacological potential. They are able to modulate the activity of many enzymes involved in metabolism and are found among antibacterial, antifungal, anti-inflammatory, antioxidant, and antiproliferative drugs. A new thiazolyl-triazole SB was obtained and characterized by elemental and spectral analysis. The antibacterial and antifungal ability of the SB was evaluated against Gram-positive and Gram-negative bacteria and against three Candida strains. SB showed good antibacterial activity against L. monocytogenes and P. aeruginosa ; it was two times more active than ciprofloxacin. Anti- Candida activity was twofold higher compared with that of fluconazole. The effect of the SB on cell viability was evaluated by colorimetric measurement on cell cultures exposed to various SB concentrations. The ability of the SB to modulate oxidative stress was assessed by measuring MDA, TNF- α, SOD1, COX2, and NOS2 levels in vitro, using human endothelial cell cultures exposed to a glucose-enriched medium. SB did not change the morphology of the cells. Experimental findings indicate that the newly synthetized Schiff base has antibacterial activity, especially on the Gram-negative P. aeruginosa, and antifungal activity. SB also showed antioxidant and anti-inflammatory activities.